Explaining mass balance and retreat dichotomies at Taku and Lemon Creek Glaciers, Alaska - Christopher McNeil; Shad O'Neel; Michael Loso; Mauri Pelto; Louis Sass; Emily H. Baker; Seth Campbell (Journal of Glaciology, 2020)
We reanalyzed mass balance records at Taku and Lemon Creek Glaciers to better understand the relative roles of hypsometry, local climate and dynamics as mass balance drivers. Over the 1946–2018 period, the cumulative mass balances diverged. Tidewater Taku Glacier advanced and gained mass at an average rate of +0.25 ± 0.28 m w.e. a–1, contrasting with retreat and mass loss of −0.60 ± 0.15 m w.e. a−1 at land-terminating Lemon Creek Glacier. The uniform influence of regional climate is demonstrated by strong correlations among annual mass balance and climate data. Regional warming trends forced similar statistically significant decreases in surface mass balance after 1989: −0.83 m w.e. a–1 at Taku Glacier and −0.81 m w.e. a–1 at Lemon Creek Glacier. Divergence in cumulative mass balance arises from differences in glacier hypsometry and local climate. Since 2013 negative mass balance and glacier-wide thinning prevailed at Taku Glacier. These changes initiated terminus retreat, which could increase dramatically if calving begins. The future mass balance trajectory of Taku Glacier hinges on dynamics, likely ending the historic dichotomy between these glaciers.